Index-Futures Arbitrage and the Behavior of Stock Index Futures Prices - MacKinlay, A. Craig; Ramaswamy, Krishna (Review of Financial Studies, 1988)
[This article examines intraday transaction data for S&P 500 stock index futures prices and the intraday quotes for the underlying index. The data indicate that the futures price changes are uncorrelated and that the variability of these price changes exceeds the variability of price changes in the S&P 500 index. This excess variability of the futures over the index remains even after controlling for the nonsynchronous prices in the index quotes, which induces autocorrelation in the index changes. We advance and examine empirically two hypotheses regarding the difference between the futures price and its theoretical value: that this "mispricing" increases on average with maturity, and that it is path-dependent. Evidence supporting these hypotheses is presented.]